Ants as vectors of pathogenic microorganisms in a hospital in São Paulo county, Brazil - Máximo, Heros J; Felizatti, Henrique L; Ceccato, Marcela [UNESP]; Cintra-Socolowski, Priscila [UNESP]; Beretta, Ana Laura R Zeni (Springer Nature, 2014)
Background: The present study aimed to identify and characterize the presence of bacteria carried by ants, and check the distribution of these ants in the physical confines of a medium-sized hospital in São Paulo county, Brazil. Methods: The ants were collected from March 2012 to February 2013. Attractive non-toxic baits were used to catch the ants, and the sectors considered for the study were medical wards, outdoor areas, obstetric unit, reception area, kitchen, surgical centres, paediatric clinic and intensive care unit. Captured ants were classified using taxonomic keys and subsequently immersed in Brain Heart Infusion broth. Results: Paratrechina spp. and Monomorium floricola ants were found most frequently in the hospital. Ants had a high capacity for carrying bacteria, and the isolates comprised 68.8% Gram-positive, spore-producing bacilli (Bacillus spp. and Listeria spp.); 14.7% Gram-negative bacilli (Pseudomonas aeruginosa and Klebsiella spp.); and 16.4% Gram-positive cocci (Streptococcus spp. and Staphylococcus aureus). Among the areas being evaluated, the medical wards had the largest number of ants captured, and therefore the most bacteria. Conclusions: Ants in hospitals may carry both Gram-positive and Gram-negative bacteria, and methods of controlling urban ants should be adopted and strictly adhered to, to minimize the risk of infection in hospital patients.
Keywords: Ants; Bacteria; Nosocomial environment; Nosocomial infection; Pathogenic microorganisms